Proceedings of the 5th Information Interaction in Context Symposium 2014
DOI: 10.1145/2637002.2637021
|View full text |Cite
|
Sign up to set email alerts
|

Stuck in traffic

Abstract: In this paper we investigate how query response delays and document download delays a↵ect user interactions within a search system. Guided by Information Foraging Theory and Search Economic Theory, five competing hypotheses relating to the behaviours of searchers in the presence of delays are considered and examined in the context of ad-hoc topic retrieval. A between-subjects laboratory study with 48 undergraduate subjects was conducted. Subjects were randomly assigned to one of four conditions that varied the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
2

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…For example, Azzopardi et al [8] found that users searching on the structured interface (considered high cost) issued significantly less queries and examined significantly more documents per query than those using the lower cost interfaces. Maxwell and Azzopardi [96] observed a similar finding, with their results indicating that as the relative cost of querying increased, users issued fewer queries and examined more documents per query. As the information search task becomes more complex, users perceive higher levels of effort [91] and workload [120], and effort measures have been found to correlate with all information task characteristics associated with task difficulty (i.e., higher number of steps to achieve the task goal; intellectual task product; amorphous task goal).…”
Section: Scope Of Cost Effort and Load Research In Isrmentioning
confidence: 55%
See 2 more Smart Citations
“…For example, Azzopardi et al [8] found that users searching on the structured interface (considered high cost) issued significantly less queries and examined significantly more documents per query than those using the lower cost interfaces. Maxwell and Azzopardi [96] observed a similar finding, with their results indicating that as the relative cost of querying increased, users issued fewer queries and examined more documents per query. As the information search task becomes more complex, users perceive higher levels of effort [91] and workload [120], and effort measures have been found to correlate with all information task characteristics associated with task difficulty (i.e., higher number of steps to achieve the task goal; intellectual task product; amorphous task goal).…”
Section: Scope Of Cost Effort and Load Research In Isrmentioning
confidence: 55%
“…A study examining the effects of time delays on the Google search engine found that even a relatively small delay of 400ms in returning search results led to a reduction in the number of searches conducted by 0.59% over the course of 6-weeks [16]. Additional studies revealed similar findings, highlighting that as the cost of querying increases, the number of queries issued by the user will decrease [8,96].…”
Section: Scope Of Cost Effort and Load Research In Isrmentioning
confidence: 95%
See 1 more Smart Citation
“…Search interaction data was used in the measurement of all three CEL concepts with often the same metrics used to measure different concepts. For example, "number of queries issued", "number of documents opened", and "number of pages viewed" have been implicated as both a measure of cost [33,43] and effort [8,21,27]. Likewise, "time-on-task" was used as a metric for all CEL concepts: cost [43,62]; effort [8,48,54]; and load [13,46], implying that time-on-task is an adequate indicator of all three concepts.…”
Section: Main Issues 51 Ambiguity Between Concepts and Measuresmentioning
confidence: 99%
“…Search interaction logs cover a variety of different actions ranging from a simple mouse click to viewing a whole document. As observed from the studies [4,8,33,44,62], these actions are often "count based". However, it is not clear how we can compare, say the total number of clicks to the total number of queries examined?…”
Section: Main Issues 51 Ambiguity Between Concepts and Measuresmentioning
confidence: 99%